Competencies and challenges of seminary libraries in spiritual formation of seminarians in the Archdiocese of Manila - Calo, Wilbur S.; Olgado, Benedict S. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2016)
The specilized collection of seminary libraries is meant to support the curriuclum of academic formation in the training for the catholic priesthood. However, since spiritual formation is what markedly differentiates the seminary from other similar institutions of tertiary-education this study will seek to discover whether seminary libraries, aside from their academic purposes also play a role in the spiritual formation of their patrons.
Respondents from two seminaries within the Archdiocese of Manila participated in the study, as well as a former professor of the San Jose Seminary in Antique, who is now serving as a priest in this archdiocese. The respondents were interviewed with guide questions on topics ranging from the role of academic training in relation to the total formation of priests, to the perceptions roles and prestige that is attributed to the seminary library as a member of the community.
The results of the interviews as well as a close examination of Catholic literature revealed that it is precisely in the role of the seminary library as an information-provider in support of academic goals that a unique spiritual role in librarianship is revealed. This is due to the nature and expectations of Catholic intellectual tradition manifest in academic training. Its purposeful orientation towards the cultivation of virtue and piety immediately create a strong connection between library services, and the spiritual activity of seminary life. This conclusion is strongly supported, both by the respondent's understanding of the necessity of the academic component of seminary training, as well as by close consultation of both the canonical demands of the Church to its clerical candidates, and Holy Tradition understood in the light of Faith.
This study however has been severely limited by a purely conceptual exploration and has not been able to delve deeply into the practical aspects of library practice in seminaries, and how they manifest the unique spiritual role herein elaborated in the study's findings. It is recommended that should there be interest in the spiritual role of seminary librarianship that such areas as collection development and library management be developed on the basis of Catholic educational standards.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Church Libraries -- Philippines -- Manila; Seminarians -- Philippines -- Manila; Spiritual formation